2010
DOI: 10.1016/j.fm.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria population dynamics during minced beef storage under aerobic or modified atmosphere packaging conditions

Abstract: A total of 266 lactic acid bacteria (LAB) have been isolated from minced beef stored at 0, 5, 10 and 15 °C aerobically and under modified atmosphere packaging consisting of 40% CO(2)-30% O(2)-30% N(2) in the presence MAP (+) and absence MAP (-) of oregano essential oil. Sequencing of their 16S rRNA gene along with presence of the katA gene demonstrated dominance of the LAB microbiota by Leuconostoc spp. during aerobic storage at 5, 10 and 15 °C, as well as during MAP (-) and MAP (+) storage at 10 and 15 °C; La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 41 publications
(57 reference statements)
4
54
1
19
Order By: Relevance
“…This was something quite expected, given the well-known greater capability of L. monocytogenes to adapt to survive and grow under a wider range of environmental conditions than S. enterica (18). In order to discriminate between the three different L. monocytogenes strains with regard to their ability to contribute to the formation and maintenance of the mixed culture biofilm communities (mono-/dual species) as well as to their antimicrobial recalcitrance, a promising PFGE approach, already used by our team (15,34), was followed. In this study, PFGE analysis revealed interesting information regarding strain occurrence following the different treatments (control, BC, NaClO, PA, and HP-PA) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This was something quite expected, given the well-known greater capability of L. monocytogenes to adapt to survive and grow under a wider range of environmental conditions than S. enterica (18). In order to discriminate between the three different L. monocytogenes strains with regard to their ability to contribute to the formation and maintenance of the mixed culture biofilm communities (mono-/dual species) as well as to their antimicrobial recalcitrance, a promising PFGE approach, already used by our team (15,34), was followed. In this study, PFGE analysis revealed interesting information regarding strain occurrence following the different treatments (control, BC, NaClO, PA, and HP-PA) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The rest isolates were subjected to species identification by sequencing the V1-V3 variable region of the 16S rRNA gene with the primer PI-V1 (Doulgeraki, Paramithiotis, Kagkli, & Nychas, 2010). PCR products were purified using the QIAquick Ò PCR Purification Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions and directly sequenced by the Department of Immunology & Histocompatibility, School of Medicine, University of Thessaly (Larissa, Greece).…”
Section: Lab Characterizationmentioning
confidence: 99%
“…Currently, the focus is mainly on the systematic study of wellknown spoilage-related species (13)(14)(15)(16)(17)(18) in various food matrices and the development of methods to suppress their growth and offensive metabolism through the application of innovative technologies. The spoilage-related populations can be studied as a consortium with the help of culture-independent approaches in order to look at changes to the composition of the microbial communities in response to environmental factors related to food storage, such as temperature and packaging technology (19,20), as well as technological parameters (21).…”
mentioning
confidence: 99%